2014
DOI: 10.1111/pce.12297
|View full text |Cite
|
Sign up to set email alerts
|

Lacking chloroplasts in guard cells of crumpled leaf attenuates stomatal opening: both guard cell chloroplasts and mesophyll contribute to guard cell ATP levels

Abstract: Controversies regarding the function of guard cell chloroplasts and the contribution of mesophyll in stomatal movements have persisted for several decades. Here, by comparing the stomatal opening of guard cells with (crl-ch) or without chloroplasts (crl-no ch) in one epidermis of crl (crumpled leaf) mutant in Arabidopsis, we showed that stomatal apertures of crl-no ch were approximately 65-70% those of crl-ch and approximately 50-60% those of wild type. The weakened stomatal opening in crl-no ch could be parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 47 publications
(104 reference statements)
1
28
0
Order By: Relevance
“…Light-stimulated increases in PEPC activity have been demonstrated with enhanced malate accumulation and increased NADPor NAD-dependent MDH activity, which facilitates the reduction of OAA to malate (Rao and Anderson, 1983;Scheibe et al, 1990). A recent study using stable isotope labeling to explore guard cell metabolism revealed that tobacco guard cells fix CO 2 via both Rubisco and PEPC (Daloso et al, 2015), which agrees with earlier studies showing that guard cells have all the necessary machinery to operate the two CO 2 fixation pathways Tarczynski et al, 1989;Parvathi and Raghavendra, 1997;Zeiger et al, 2002;Outlaw, 2003;Suetsugu et al, 2014;Wang et al, 2014). The importance of PEPC in stomatal behavior has been shown by Cousins et al (2007) in PEPC-deficient mutants of the C 4 plant Amaranthus edulis, which exhibited reduced stomatal opening and low final conductance compared with wild-type plants.…”
Section: Contribution Of Pepc To Co 2 Fixation In Guard Cellssupporting
confidence: 65%
See 1 more Smart Citation
“…Light-stimulated increases in PEPC activity have been demonstrated with enhanced malate accumulation and increased NADPor NAD-dependent MDH activity, which facilitates the reduction of OAA to malate (Rao and Anderson, 1983;Scheibe et al, 1990). A recent study using stable isotope labeling to explore guard cell metabolism revealed that tobacco guard cells fix CO 2 via both Rubisco and PEPC (Daloso et al, 2015), which agrees with earlier studies showing that guard cells have all the necessary machinery to operate the two CO 2 fixation pathways Tarczynski et al, 1989;Parvathi and Raghavendra, 1997;Zeiger et al, 2002;Outlaw, 2003;Suetsugu et al, 2014;Wang et al, 2014). The importance of PEPC in stomatal behavior has been shown by Cousins et al (2007) in PEPC-deficient mutants of the C 4 plant Amaranthus edulis, which exhibited reduced stomatal opening and low final conductance compared with wild-type plants.…”
Section: Contribution Of Pepc To Co 2 Fixation In Guard Cellssupporting
confidence: 65%
“…This idea was supported by Reckmann et al (1990) Baroli et al, 2008). However, Wang et al (2014) found that, in an Arabidopsis crumpled leaf mutant (cr1), stomatal aperture in plants lacking guard cell chloroplasts (cr1-no chl) was 30% to 40% smaller than that of plants with guard cell chloroplasts (cr1-chl) and 40% to 50% smaller than that of the wild type, perhaps likely due to reduced ATP levels in their guard cells (and in the adjacent epidermal cells). These studies provide evidence that both guard cell chloroplasts and mesophyll contribute to ATP for H + extrusion in guard cells and that guard cell chloroplasts play an essential role in light-induced stomatal opening .…”
Section: Role Of Guard Cell Chloroplast In Stomatal Movementsmentioning
confidence: 98%
“…; Wang et al . ). However, the mode of CO 2 fixation and hence the relative contribution of the Calvin–Benson cycle to stomatal function is still unclear (Lawson ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, photosynthetic processes in guard cell chloroplasts provide fuel (ATP and/or reducing equivalents) for blue light-dependent H + pumping of the PM H + -ATPase and contribute to stomatal opening (Suetsugu et al, 2014). Correspondingly, guard cells lacking chloroplasts in the crumpled leaf mutant displayed attenuation of both guard cell ATP levels and stomatal opening in response to light (Wang et al, 2014). Stored triacylglycerols in guard cells are broken down in response to light and the catabolic process is also thought to supply ATP for PM H + -ATPase activity in stomatal opening (McLachlan et al, 2016).…”
Section: Blue Light Signaling For Stomatal Openingmentioning
confidence: 99%